MY CART (5)

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: R

There are no items in this cart.
Continue Shopping
                   

evaluate  ∫[ex(1-x2) / (1+x2)]dx


 how can i write it in mathematical way by computer ? i mean to say from where i get mathematical tool .

3 years ago

Share

Answers : (2)

                                        

i think that facility is not providing by askiitians


 


any way try it

3 years ago
                                        

Download MathType, a free download software for typing all mathematical equations. It is a trial version for 30 days but you can either buy it, or uninstall and install it every 30 days.

3 years ago

Post Your Answer

More Questions On Integral Calculus

Ask Experts

Have any Question? Ask Experts

Post Question

 
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!!
Click Here for details
What will be the anti derivative of e 3x ? Is there any method other than substitution to solve it?
 
 
Anti derivative of e 3x = ∫ e 3x dx = e 3x /3 + c I think substitution is the simplest way(substitute 3x for t) or just do it directly
 
Harikrishnan M B 11 months ago
3 ∫ 0 ( x + 4) dx
 
 
Ans:- 3 ∫ 0 (x+4)dx =[(x 2 /2)+4x] 0 3 =[(3 2 /2)+4(3)] =[(9/2)+12] =(9+24)/2 =33/2
 
Anusha 8 months ago
integration of logx2
 
 
log x 2 = 2 logx and integration of logx is =xlogx – x,,using ILATE so the answer is 2(xlogx -x)
 
himanshu pandey 5 months ago
 
log x 2 = 2 log x So its answer is = 2( x logx + x ) Please approve if you like it
 
Shivam Chopra 5 months ago
Tan6°*tan42°*tan66°*tan78° = 1
 
 
proof of tan@ * tan (60 – @) * tan (60+@) = tan3@ just change all the expression in terms of sin and cos then change the sin (60 – @) * sin (60+@) / cos (60 – @) * cos (60+@) expression...
 
Kaustubh Nayyar 4 months ago
 
we know that tan@*tan(60-@)*tan(60+@) = tan (3@) just using this we get tan18 * tan 42 * tan 78 = tan 54 hence ur given expression becomes (tan 6 * tan 66 * tan 54) * cot18 = tan 18 * cot18 ...
 
Kaustubh Nayyar 4 months ago
f:X to Y f(x)=sinx+cox+2root2 is invertible then X to Y is
 
 
Hello Student, Thanks & Regards Arun Kumar Btech, IIT Delhi Askiitians Faculty
  img
Arun Kumar 11 months ago
solve mod x^2 +4x +3=x+1.
 
 
|x 2 +4x+3|=x+1, Now, the LHS changes at different values of x. x 2 +4x+3=(x+3)(x+1)=+ve for x -1 ...(i) while it is -ve for x between -3 and -1 ...(ii) So, for (i) we have x 2 +4x+3=x+1 on ...
 
Shubham Swastik Behera one month ago
 
Something is wrong with the greater than and less than symbol. I’m writing it in words: x 2 +4x+3=(x+3)(x+1)=+ve for when x is outside (-3,-1) i.e. less than -3 and greater than -1. Cheers!!
 
Shubham Swastik Behera one month ago
 
x 2 + 4x + 3 = x +1 x 2 + 3x +x + 3 = x + 1 (splitting the middle term) x(x+3) 1(x+3) = x + 1 (x+1)(x+3) = x+1 x+3 = x+1/x+1 x+3 = 1 x= 1-3= -2
 
sakthi meena Ramanathan one month ago
View all Questions »